167 What Is the Impact of Obesity in MIS vs OPEN Surgery for Adult Spinal Deformity?. (August 2015) - Park, Paul; Mummaneni, Praveen V.; La Marca, Frank; Fu, Kai-Ming G.; Nguyen, Stacie; Wang, Michael Y.; Uribe, Juan S.; Anand, Neel; Mundis, Gregory; Deviren, Vedat; Kanter, Adam S.; Fessler, Richard G.; et al.
Abstract : INTRODUCTION: Obesity is a significant comorbidity that can increase the risk and technical difficulty of surgery. Previous studies comparing minimally invasive (MIS) to traditional open spinal surgery in the obese have shown similar clinical outcomes but improved perioperative benefits of decreased estimated blood loss (EBL), length of stay (LOS), and complications with MIS approaches. Similar studies have not been performed for obese patients undergoing surgery for adult spinal deformity (ASD). This study's objective was to compare the impact of obesity in the treatment of ASD with MIS compared with open approaches. METHODS: Two multicenter databases, one involving MIS surgeries and the other open surgeries, were queried. Inclusion criteria for both databases were diagnosis of ASD, minimum 2-year follow-up, and at least 1 of the following parameters: coronal cobb (CC) = 20°, SVA > 5 cm, PT > 25°, thoracic kyphosis > 60°. Patients with body mass index (BMI) = 30 were identified and then propensity matched for levels fused. Thirty-eight patients with 19 in each group were analyzed. RESULTS: Patients were well matched with mean ages of 65.4 and 64.3 years and BMI 34.7 and 34.0, respectively, for the MIS and open groups. Table 1 lists outcomes between the groups. Mean levels fused were 4.2 for MIS and 2.7 for open. Statistically significant improvement in Oswestry Disability Index (ODI) and Visual Analog Scale (VAS) were noted within each group. Notably, there was no significant difference in radiographic parameters or ODI and VAS scores between groups. A significant decrease in EBL was noted in the MIS group; however, complications and reoperation frequency were not statistically different. CONCLUSION: Similar clinical and radiographic improvements were noted for MIS and open treatment of ASD. Although EBL was less in the MIS group, the frequency of complications and reoperations were similar, suggesting the potential benefit of MIS approaches may be mitigated by obesity. Larger comparative studies are needed to clarify the benefit of MIS in the obese undergoing ASD surgery.